Edaphic and plant inhabiting oribatid mites (Acari: Oribatida) from Cerrado and Mata Atlantica ecosystems in the State of São Paulo, southeast Brazil - Oliveira, Anibal R.; Norton, Roy A.; de Moraes, Gilberto J. (Zootaxa, 2005)
Forest sites in the eastern half of the State of São Paulo were surveyed to determine the oribatid mite fauna in areas of Cerrado (dry savannah) and Mata Atlântica (tropical rain forest) ecosystems. Samples of bark, fruits, leaves, litter, soil and terminal shoots were taken from selected species of Myrtaceae (Cerrado) and Arecaceae (Mata Atlântica). Fifty-six oribatid species, belonging to 48 genera in 34 families, were represented. Seven of these are new records for the State of São Paulo, and 20 are new records for Brazil.